2011
DOI: 10.1016/j.sab.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Hardness determination of bio-ceramics using Laser-Induced Breakdown Spectroscopy

Abstract: Abstract:Laser-Induced Breakdown Spectroscopy (LIBS) was applied to the analysis of bioceramic samples. The relationship between sample hardness and LIBS plasma properties was investigated, with comparison to conventional Vickers hardness measurements. The plasma excitation temperature T e was determined using the lineto-continuum ratio for the Si (I) 288.16 nm emission line; we have demonstrated a linear relationship between sample surface hardness and plasma temperature. Results indicate that hardness determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 41 publications
(58 reference statements)
4
15
0
Order By: Relevance
“…It is observed that plasma temperature and Vickers hardness (Table 5) follows the order 100 kGy < 50 kGy < 0 kGy for Sample S1 but the other samples show negligible variation in plasma temperature and Vickers hardness. In several studies, it is stated that plasma temperature is directly proportional to the hardness of the material [26]. In the present study also hardness varies as 100 kGy < 50 kGy < 0 kGy for Sample S1.…”
Section: Water Diffusion Characteristicssupporting
confidence: 57%
“…It is observed that plasma temperature and Vickers hardness (Table 5) follows the order 100 kGy < 50 kGy < 0 kGy for Sample S1 but the other samples show negligible variation in plasma temperature and Vickers hardness. In several studies, it is stated that plasma temperature is directly proportional to the hardness of the material [26]. In the present study also hardness varies as 100 kGy < 50 kGy < 0 kGy for Sample S1.…”
Section: Water Diffusion Characteristicssupporting
confidence: 57%
“…The intensity ratio calculated between the ionic line and the atomic spectral line of zirconium is found to have a direct correlation with the Vickers hardness of the specimen (Table 7). Cowpe et al in [48] observed that the plasma temperature of the bio‐ceramic sample increases with increasing hardness of the sample. Abdel‐Salam et al [49] stated that the Vickers hardness number of human teeth, shellfish, and eggshells are proportional to the intensity ratios between the ion line and the atomic line for calcium and magnesium in the plasma spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…IN has highest plasma temperature. Cowpe et al [34] explored the impact of the hardness of bio‐ceramic sample on plasma temperature and observed that the plasma temperature increases with increasing sample hardness. The outcome was additionally affirmed by the investigation led by Labutin et al in which the temperature of Li–Al alloy plasma was proportional to micro‐hardness of the alloy samples [35].…”
Section: Resultsmentioning
confidence: 99%